151k views
0 votes
Graph the equations to solve the system y=-2x-3 y=x+6

User TimeIsNear
by
4.8k points

1 Answer

0 votes

Answer:Simplifying

y = -2x + -3

Reorder the terms:

y = -3 + -2x

Solving

y = -3 + -2x

Solving for variable 'y'.

Move all terms containing y to the left, all other terms to the right.

Simplifying

y = -3 + -2x

Step-by-step explanation:Simplifying

y = x + 6

Reorder the terms:

y = 6 + x

Solving

y = 6 + x

Solving for variable 'y'.

Move all terms containing y to the left, all other terms to the right.

Simplifying

y = 6 + x

User ShivamD
by
4.5k points